2022
DOI: 10.3390/app13010363
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Profile, Mineral Composition, and Health Implications of Consuming Dried Sago Grubs (Rhynchophorus ferrugineus)

Abstract: A comprehensive evaluation of the fatty acid and mineral composition of Rhynchophorus ferrugineus (sago grub powder, SGP), pre-treated to meet New Zealand import biosecurity requirements, was investigated. Palmitic acid (42.5% FA), oleic acid (39.0% FA), and linoleic acid (1.02% FA) were the most abundant saturated fatty acid, monounsaturated fatty acid, and polyunsaturated fatty acid, respectively. Lipid nutritional indices of SGP fats were ω6/ω3 (2.17), hypocholesterolemic/hypercholesterolemic acid ratio (0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 58 publications
1
0
0
Order By: Relevance
“…Consequently, in terms of human nutrition, the fat from insect species like Tenebrio molitor , Acheta domesticus , and Gryllus bimaculatus demonstrates a more favorable PUFA/SFA ratio than Rhynchophorus ferrugineus. The fat content and fatty acid profile of the tested insects were similar to the results of other studies [ 43 , 44 , 45 ].…”
Section: Resultssupporting
confidence: 88%
“…Consequently, in terms of human nutrition, the fat from insect species like Tenebrio molitor , Acheta domesticus , and Gryllus bimaculatus demonstrates a more favorable PUFA/SFA ratio than Rhynchophorus ferrugineus. The fat content and fatty acid profile of the tested insects were similar to the results of other studies [ 43 , 44 , 45 ].…”
Section: Resultssupporting
confidence: 88%
“…For example, selling RPW larvae for food or as food supplements requires legislative action by government and commercial licensing, and many countries have established laws regulating the importation of edible insect materials to control this risk. For instance, live RPW and other edible insects are not allowed to be imported into New Zealand, but they can be traded through a biosecurity pre-treatment requirement involving the boiling, drying and so on [74]. Thus, biosecurity pre-treatment represents a mutually beneficial solution for both traders and consumers.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Another study showed that differences in food source of R. ferrugineus resulted in different fatty acid compositions, although with similar amounts of total fat and total fatty acids, as well as the same types of fatty acids which were myristic, palmitic, stearic, palmitoleic, oleic, and α-linolenic acids [28]. Kavle et al [29] observed 44 minerals in R. ferrugineus larvae, including 11 essential minerals, 29 non-essential minerals, and four heavy metals. R. ferruginous larvae also contain an abundance of macro elements such as magnesium, calcium, potassium, sodium, and phosphorus and microelements such as iron, zinc, manganese, and copper.…”
Section: Composition Of R Ferrugineus Larvaementioning
confidence: 99%
“…However, R. ferrugineus is a safe, insect-derived, and natural antimicrobial agent with a broad spectrum and a low likelihood of inducing antibiotic resistance [8,12,49]. However, the low toxicity of R. ferrugineus [19,29] supports the notion that it is a safe, insect-derived, and natural antimicrobial agent with a broad spectrum and low likelihood of inducing antibiotic resistance [8,12,49].…”
Section: Comparison Of R Ferrugineus Safety Profile To Traditional An...mentioning
confidence: 99%